Response to ovarian diathermy in women with clomiphene citrate resistant polycystic ovarian syndrome. - Herath, H.M.C (My University, 2008)
This is a Prospective non randomized interventional study. 48 women, those who had clomifene citrate resistant anovulatory PCOS who admitted to ward 18, teaching Hospital Peradeniya for LOD were recruited for this study. Blood Samples were collected for early follicular FSH and LH levels preoperatively. 48 selected women had undergone LOD under general anesthesia. Relevant laparoscopic findings were documented. Postoperatively they were assessed in each cycle in between day 10-12 for follicular 1 development by trans vaginal scan. Serum FSH and LH were assessed at 6 weeks and at 6 months. Mean preoperative, LH: FSH ratio was 2.3, however at 6 weeks the ratio was 1.3andsubsequentlyat6montbs the FSH/LH was 1.4. Therefore the observed difference at 6 weeks and at 6 months was statistically significant with t values of 4.5 and 4.4 respectively